Antioxidant Activity and Essential Oil Content in Butterfly Pea Flower Herbal Tea (Clitoria ternatea) and Siam Orange Peel Extract (Citrus nobilis) Encapsulated - Anggraini, Tuty; Yenrina, Rina; Salisma, Marlis; Syukri, Daimon (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aims to determine the antioxidant activity and essential oil content in a mixture of butterfly pea flower herbal tea and encapsulated siam orange peel extract with the best characteristics. The design used in this study was a completely randomized design (CRD) with five treatments and three replications. The treatments given in this study were A (without mixing encapsulated siam orange peel extract), B (mixing encapsulated siam orange peel extract 1%), C (mixing encapsulated Siamese orange peel extract 2%), D (mixing encapsulated siam orange peel extract 3%), E (mixing encapsulated siam orange peel extract 4%). The research data were analyzed statistically using ANOVA and continued with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that the ratio of mixing encapsulated siam orange peel extract had a significantly different effect on water content, pH value, anthocyanin content, and antioxidant activity. The more the encapsulated siam orange peel extract is mixed, the higher the water content, the lower the pH value, the lower the anthocyanin content, the lower the antioxidant activity, and the higher the essential oil content as limonene, which is 3.90%. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land